2023
DOI: 10.1002/adpr.202200356
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electromagnetic Responses in Terahertz Metasurface by Breaking the Structural Symmetry in T‐Shaped Resonators

Abstract: Herein, the design of terahertz metasurface with symmetric T‐shaped resonators and the corresponding bright and dark modes are reported on. It is demonstrated that the dark mode evoked by breaking the structural symmetry is insensitive to the X‐polarized electric field and a typical electromagnetically induced transparency (EIT) effect is also observed in the numerical simulation when introducing a relatively low structural asymmetry where the dark and bright modes are modified to the same frequency. To explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…6,7 Recently, electromagnetically induced transparency (EIT) arising from quantum interference in three-level atomic systems has been extended to metasurfaces for the realizations of slow-light devices, 8,9 absorbers, 10 modulators, 11 and biosensors. 12,13 In 2008, Zhang et al 9 demonstrated a plasmonic metamaterial to investigate theoretically EIT phenomena resulting from a radiative element coupled with a subradiant (dark) element. Gu et al 11 achieved an active optical control of EIT metasurface by integrating photoconductive silicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recently, electromagnetically induced transparency (EIT) arising from quantum interference in three-level atomic systems has been extended to metasurfaces for the realizations of slow-light devices, 8,9 absorbers, 10 modulators, 11 and biosensors. 12,13 In 2008, Zhang et al 9 demonstrated a plasmonic metamaterial to investigate theoretically EIT phenomena resulting from a radiative element coupled with a subradiant (dark) element. Gu et al 11 achieved an active optical control of EIT metasurface by integrating photoconductive silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al 11 achieved an active optical control of EIT metasurface by integrating photoconductive silicon. Kang et al 12 proposed a T-shaped EIT resonator, which was attributed to the coupling between bright and dark modes as well as to the structural-symmetry breaking. More recently, EIT metamaterials are especially attractive for bio-sensing applications because of their multiple resonance modes, including two absorption dips and one transparency peak.…”
Section: Introductionmentioning
confidence: 99%